Analysis of flow-induced vibration of wire-wrapped fuel assemblies under the liquid metal axial flow in the Gen-IV nuclear reactor. (August 2023) - Guo, Hongjian; Li, Wei; Zhang, Jing; Wu, Yingwei; Wang, Mingjun; Qiu, Suizheng; Su, G.H.; Tian, Wenxi
Highlights: In order to study the fluid-induced vibration of the fuel rod of a lead-cooled fast reactor core, we developed a geometric model of the wire-wrapped fuel assembly. A detailed flow field analysis of the multi-pitch wire winding assembly case was carried out using large eddy simulation method. A unidirectional fluid–structure coupling method was used to simulate the vibration of the fuel rod due to the fluctuation of fluid excitation force. A combination of time domain and frequency domain analysis was used to analyze the fluid excitation force fluctuations and fuel rod vibration. The amplitude analysis of the fuel rod at different positions in the assembly was analyzed, and the statistical histograms were drawn. Abstract: Fluid excitation force is the root cause of flow-induced vibration in the fast reactor core, which is an important cause of nuclear fuel failure and breakage phenomena. In this study, the fluid–structure interaction (FSI) of a filament-wound rod bundles consisting of seven rods in a lead–bismuth fast reactor was simulated. And the fluctuation of fluid excitation force, as well as the vibration displacement and vibration frequency of fuel rods were calculated. It was found that when the fluid flow through the winding wire, the turbulence intensity increases significantly and pressure difference appear on the winding wire windward and leeward surface, which leads to fluctuation in the fluid force, which is the root cause of the emergence of flow-induced vibration. In this structural model, the vibration eventually reach a stable amplitude as well as position, and no pin-to-pin contact occurs.